Identifying the finance skill sets needed for a large multi-national agricultural company agricultural company - Daesch, Nanci (Kansas State University, 2013)
The world is an ever-changing place with many demands on both companies and their employees. Finance individuals in a large multi-national company also have many demands placed on them as they grow and develop with the companies in which they work. A detailed analysis was performed on one large multi-national company in the agriculture sector to determine: 1. a framework to assess the skills that finance individuals need, 2. the desired skills and needs of the finance organization, 3. a current assessment of finance experiences and skills, and 4. the gaps between the current state and the desired skill level state. Although there are a number of criteria and competencies that can be used for assessment, this thesis focused on the critical skills and experiences for two key areas: 1. accounting and technical skills, and 2. analytical and business acumen skills. Skill set levels were measured at three criteria levels: Basic, Intermediate and Advanced. The desired state of the organization and the current state of the organization was defined and mapped on a Skill Set Grid and gaps were identified. When looking at the results, the data indicate that Company XYZ has several areas to explore further and refine. There were many gaps in the current state of the skill sets versus the desired state of the skill sets in both the areas of accounting and technical skills and analytical and business acumen skills. Further, the analytical and business acumen skills were significantly in need of further improvement. In addition, several areas of further refinement could occur that would further enhance the use of this skill assessment methodology. However, both the company and the employees who received feedback valued the information developed in this process.
Keywords: Gap analysis; Finance skills; Business acumen; Accounting skills